2022
DOI: 10.1016/j.bbamem.2021.183837
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous binding of the N- and C-terminal cytoplasmic domains of aquaporin 4 to calmodulin

Abstract: Aquaporin 4 (AQP4) is a water transporting, transmembrane channel protein that has important regulatory roles in maintaining cellular water homeostasis. Several other AQP proteins exhibit calmodulin (CaM)-binding properties, and CaM has recently been implicated in the cell surface localization of AQP4 that occurs in response to osmotically-driven changes in cell swelling in the central nervous system. The objective of the present study was to assess the CaM-binding properties of AQP4 in detail. Inspection of A… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…Given that a structure-based drug design targeting individual AQPs remains challenging despite intense efforts [186][187][188][189][190], switching the focus to the AQP interactome may offer new therapeutics avenues for the treatment of human disease states in which AQPs play an important role. CaM C-term [111,126]; N-term [126] MST [111]; NMR [126] DGC ND IP [193][194][195]…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Given that a structure-based drug design targeting individual AQPs remains challenging despite intense efforts [186][187][188][189][190], switching the focus to the AQP interactome may offer new therapeutics avenues for the treatment of human disease states in which AQPs play an important role. CaM C-term [111,126]; N-term [126] MST [111]; NMR [126] DGC ND IP [193][194][195]…”
Section: Discussionmentioning
confidence: 99%
“…A recent study using AQP4 N- and C-terminal peptides revealed CaM-binding domains located within both termini, with the N-terminus interacting with the N-lobe of calmodulin (Kd: 3.4 ± 0.8 µM, 1:1 binding ratio) and the C-terminus interacting with both the C- and N-lobes of CaM (Kd1: 3.6 ± 1.3 µM; Kd2: 113.6 ± 8.0 µM, 2:1 binding ratio). Moreover, both peptides could interact with CaM simultaneously, forming a ternary complex [ 126 ]; however, it remains to be established if this is also possible in the full-length context. It has been debated whether the AQP4–CaM interaction is strengthened [ 111 ] or not [ 126 ] upon AQP4 phosphorylation at Ser276, a PKA site that has been shown to be involved in AQP4 plasma membrane localization [ 111 ].…”
Section: Aqp4mentioning
confidence: 99%
See 1 more Smart Citation
“…From the viewpoint of aquaporin regulation, it is intriguing that all CWLP-interacting PP2A-B’’ subunits contain EF-hand motifs similar to those of calmodulins (CaMs). Whereas the 8CM domain of Arabidopsis snLTP1 is found to bind calmodulin (CaM) in a Ca 2+ -dependent manner (169), CaM-binding to human aquaporins inhibits their activity, which is counteracted by phosphorylation of C-terminal Ser residues (170). Therefore, additional studies of DRM complexes are required to determine whether calmodulins, other cargos, protein kinases, known scaffold proteins, signaling factors, and AF network components are associated with CWLP- and PRP940-marked nanodomains.…”
Section: Discussionmentioning
confidence: 99%
“…The most well understood is that of AQP2, which is expressed in the kidney collecting duct and is triggered by vasopressin (Centrone et al., 2022). The trafficking mechanism of AQP4 has been shown to be calmodulin (CaM) and phosphorylation dependent (Ishida et al., 2022; Kitchen, Day, Salman, et al., 2015; Kitchen, Day, Taylor, et al., 2015). Triggered by changes to the extracellular environment, Ca 2+ ions enter the cell via TRPV4 channels and activate calmodulin.…”
Section: Introductionmentioning
confidence: 99%